Analisis Konstruksi Posisi Lightning Arrester di Gardu Distribusi Km 0003 Penyulang Subagan Wilayah Kerja PT PLN (Persero) ULP Karangasem - I Made Sariana; I Made Asna; I Wayan Sugarayasa (Universitas Pendidikan Nasional, 2020)
One of the system distribution components is the substation distribution. Distribution substation connects the network to consumers. The most important components of a distribution substation is the transformer . Transformers often experience interference due to lightning strikes since the position is in the open air. During the period of time 2017 -2019 on feeder Subagan suffered disruption due to the impulse of lightning for 10 times. The study aim to discuss how the work of lightning arresters in protecting equipment with the construction of the old model and after made changes in the position , distance protection ideal lightning arrester to the transformer , performance lightning arrester after changes in position on the new construction , and the impact of differences in the construction of the installation of lightning arresters in ULP Karangasem . From the analysis , through the climate condition in the region of Karangasem, the maximum lightning distance protection arrester and the transformer is 6.2245 meters. Distance lightning of the old construction existing arrester and transformer was 1,5 meters. The distance that makes the current peak of lightning that is capable received from lightning arrester amounted to 178.3032 kA, so it can be concluded that the distance lightning arrester and transformer with long construction can work with the maximum. The new construction, according to SPLN D5.006 2013, the distance of lightning arrester and transformer in KM 0003 was 0.6 meters. The distance that makes the current peak of lightning that is capable received from lightning arrester is higher, namely 655.008 kA, and increase the performance of lightning arresters for 267.36 % due to changes in position.